INDELIBLE FACIAL DISFIGUREMENT: FROM MEDICAL TO LEGAL ASSESSMENT - Mytrofanov, I.I.; Lysenko, I.V.; Ryabushko, M.M. (World of Medicine and Biology, 2018)
Among crimes against human health, we distinguish grave bodily injury and irreparable facial maim is recognized as one of its peculiar features. It is this feature that still remains as a controversial and insufficiently defined procedure for its constating. The latter one affects the practice of applying Article 121 of the Criminal Code of Ukraine, which results in miscarriages of justice. One of the reasons for miscarriages of justice is in evaluating the irreparable facial maim. According to the Rules of forensic assessment of the severity of bodily injuries, approved by the Order of the Ministry of Health of Ukraine, No. 6 dated from 17 January 1995, it is stated that a forensic expert does not qualify a person's injury as maim because this notion is not a medical one.The purpose of the work was to develop criteria and procedures for determining the irregularity of facial maim as a sign of grave bodily injury, the responsibility for which is established by Art. 121 of the Criminal Code of Ukraine. Surveys of the victims and their medical documents show that in case of irreparable injury of the face, the person’s physical, mental and social well-being is affected, therefore, during the forensic medical examination, a complex judicial expertise should be appointed and carried out with the involvement of Articles 242 and 243 of the Criminal Code of Ukraine, a forensic medical expert, a surgeon-cosmetologist (plastic surgeon), a psychiatrist, the results of the expertise are concluded on the basis of Art. 101 and 102 of the Criminal Code of Ukraine. Only the complex nature of the examination will permit the expert to form the correct opinion on remediableness or non-remediableness of the facial injury and will deprive the lawyers (investigator, prosecutor, judge) of assessing irreparable damage to the person as a maiming of the latter. Thus, actually, more than 70% of the polled lawyers believe that the definition of facial injury as a maiming of the person is a medical matter rather than a legal one. Almost half of respondents point to the necessity of such a definition by a complex judicial forensic examination. Other questionnaires related to the other five signs of grave bodily injury, which is a continuation of this study and will be made public in a separate scientific article.The results obtained permitted to detect gaps in the regulation of the way of establishing reparable or irreparable damage of facial maim. The ways of further improvement of the procedure of carrying out expert investigations of facial maim as irreparable are found, which will help to avoid miscarriages of justice in forensic practice. The Rules are to be amended in order to determine the irreparable damage of facial maim by consolidating the way of such definition by a comprehensive judicial expertise consisting of a forensic expert, a surgeon-cosmetologist (plastic surgeon), a psychiatrist, which will result in making a conclusion on the reparable or irreparable damage of facial maim.
Keywords: facial disfigurement; indelibility of facial disfigurement; medical indices of indelibility of facial disfigurement; legal assessment of the indelibility of facial disfigurement; the procedure for assessing the indelibility of facial disfigurement